2019
DOI: 10.3390/md17020107
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Composition and Revenue Explained by Interactions between Extrinsic Factors and Endogenous Rhythms of Saccharina latissima

Abstract: This review provides a systematic overview of the spatial and temporal variations in the content of biomolecular constituents of Saccharina latissima on the basis of 34 currently-available scientific studies containing primary measurements. We demonstrate the potential revenue of seaweed production and biorefinery systems by compiling a product portfolio of high-value extract products. An investigation into the endogenous rhythms and extrinsic factors that impact the biomolecular composition of S. latissima is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 155 publications
(225 reference statements)
2
25
1
Order By: Relevance
“…The DM content of pre-ensiling Alaria and Saccharina in present study was low but within the previously reported range of 5 to 36% DM in macroalgae (Zhang & Thomsen 2019) and was lower than that of the wild biomass collected in a close region (Tayyab et al 2016;Novoa-Garrido et al 2020). The chemical composition was within the range of the reported seasonal variation (Table 1) (Schiener et al, 2015).…”
Section: Pre-ensiling Biomasssupporting
confidence: 85%
“…The DM content of pre-ensiling Alaria and Saccharina in present study was low but within the previously reported range of 5 to 36% DM in macroalgae (Zhang & Thomsen 2019) and was lower than that of the wild biomass collected in a close region (Tayyab et al 2016;Novoa-Garrido et al 2020). The chemical composition was within the range of the reported seasonal variation (Table 1) (Schiener et al, 2015).…”
Section: Pre-ensiling Biomasssupporting
confidence: 85%
“…For instance, they include ulvan, a sulfated glucuronoxylorhamnan, in green macroalgae Ulva lactuca [5]; alginate and sulfated polysaccharides, such as fucoidan, in brown macroalgae, such as Saccharina latissima, Laminaria digitata, and Fucus vesiculosus [4,6,7]. Macromolecular composition of seaweed is also varied with seasons and nutrient availability [8,9]. For instance, it has been shown that the highest carbohydrate content was in spring [10] and summer [11] in green seaweed, U. lactuca, with increased rhamnosyl and glucuronoyl residues in April [10].…”
Section: Introductionmentioning
confidence: 99%
“…The biorefinery approach (algae biofactory) is currently being investigated as a mean to increase the environmental sustainability and economic feasibility of existing conventional industrial processes. Different potential conversion pathways are being researched for the use, extraction and valorization of algae biomass biorefinery products (Zhang and Thomsen, 2019). Additionally, technological improvements in the biomass cultivation systems are intensively researched (e.g., offshore aquaculture, biomass optimization practices, technology readiness for microalgae production and processing, incorporation of algae production in wastewater treatment and CO 2 mitigation).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the role of seasonal, environmental and geographical variation in the nutritional properties of seaweeds needs to be better documented to support nutritional claims (Wells et al, 2016). Seaweed biomolecular composition can change markedly in response to seasonal variation in environmental factors such as salinity, nitrogen content and water temperature (Marinho-Soriano et al, 2006;Zhang and Thomsen, 2019).…”
Section: Biomass Applicationsmentioning
confidence: 99%